Raising Awareness: Real World Data On Palliative Care for Advanced Pediatric Cancers in Bavaria - Nehls, Nadja; Börner, Maja; Ziegelmayer, Sebastian; Haller, Bernhard; Klot, Felicitas Ferrari von; Metzler, Markus; Frühwald, Michael C.; Schlegel, Paul Gerhardt; Corbacioglu, Selim; Feuchtinger, Tobias; Lüttichau, Irene Teichert von (Pediatric Blood & Cancer, 2025)
Introduction: Early integration of palliative care in children with cancer provides a variety of positive effects and is recommended at diagnosis. However, barriers often delay its implementation, and palliative care remains underutilized. This study provides real-world data on palliative care and integration in pediatric oncology in a high-income country. Methods: In this retrospective observational study, data derived from patients with refractory, progressive, or relapsed malignancies under the age of 18 years were collected from six German pediatric oncology centers (2017–2022). In addition to palliative data (onset, and duration of palliative care services, frequency of contact, place of death), disease entity, relapse/progression frequency, Karnofsky Performance Scale Index, therapy, and overall survival were collected. The frequency, timepoint of initiation and the duration of palliative care services were examined in relation to the disease trajectory (diagnosis to death/censoring) and tumor entity. Outcomes (overall survival, Karnofsky Performance Scale Index, place of death) were analyzed based on palliative care status. Results: Only 157 (42%) of the 373 patients received palliative care services. The mean duration of palliative involvement was 6.0 months with a mean disease trajectory of 31.4 months for patients receiving palliative care. On average, palliative care was initiated in the last third of the disease trajectory. Most of the 157 patients (65.9%) received palliative care during their final relapse/progression and only 16.8% at diagnosis. There was a significantly lower frequency of palliative care involvement for children with hematological malignancies. Conclusion: Despite the substantial benefits, this study highlights significant delays and underutilization of palliative care for pediatric oncology patients, even in a high-income country.
CRIS-Team Scopus Importer:2025-07-04
Keywords: cancer; high-income country; palliative care; pediatric oncology; real-world data; underutilization palliative care